2010
DOI: 10.1111/j.1365-2621.2010.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Aroma profile of Niagara grape juice contaminated with multicoloured Asian lady beetle taint using gas chromatography/mass spectrometry/olfactometry

Abstract: The objective of this study was to determine the odour-active compounds present in Niagara grape juice tainted with multicoloured Asian lady beetle (MALB: Harmonia axyridis: Coleoptera: coccinellidae). Niagara grape juice was made with (2.5 MALB ⁄ L) and without MALB and evaluated using solid-phase microextraction coupled with gas chromatography ⁄ mass spectrometry ⁄ olfactometry (GC ⁄ MS ⁄ O) to tentatively identify compounds. Compared to the control juice, phenol, described as musty ⁄ mouldy, was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…For SBMP, higher concentrations are observed in MALB‐affected wines than in 7 Spot or control wines for both varietals. These findings are in partial agreement with Ross et al who detected SBMP in MALB‐treated Niagara juice, but not in untreated juice. The results from the current study suggest a possible role for SBMP in MALB‐tainted wine, as the human sensory threshold for this compound (in water) is 1–2 ng L −1 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For SBMP, higher concentrations are observed in MALB‐affected wines than in 7 Spot or control wines for both varietals. These findings are in partial agreement with Ross et al who detected SBMP in MALB‐treated Niagara juice, but not in untreated juice. The results from the current study suggest a possible role for SBMP in MALB‐tainted wine, as the human sensory threshold for this compound (in water) is 1–2 ng L −1 .…”
Section: Resultssupporting
confidence: 92%
“…Most of the studies seeking to identify the compounds responsible for LBT have employed gas chromatography–mass spectrometry (GC‐MS). One study employed gas chromatography mass spectrometry coupled with olfactometry (GC‐MS‐O) to identify and characterize the odor active compounds in live MALB and one used GC‐MS‐O to determine the compounds associated with LBT in grape juice . GC‐MS‐O has not been used to date to characterize wines tainted by MALB or 7 Spot.…”
Section: Introductionmentioning
confidence: 99%
“…The specific MP(s) responsible for LBT of wine is more equivocal in the literature. While IPMP is the putative candidate, questions are raised by the lack of such finding by Galvan et al ., the co‐elution of some MPs in the aforementioned study of Botezatu and Pickering (their Table 5) and a suggested contribution from SBMP or IBMP in grape juice and wine …”
Section: Discussionmentioning
confidence: 99%
“…Target chemical species for such research could include alkaloids, as Pickering et al . reported increased bitterness in Coccinellidae‐affected wines, and decanal …”
Section: Discussionmentioning
confidence: 99%
“…, 2005, 2007, 2008a,b; Galvan et al. , 2008; Ross et al. , 2010), and ladybugs release these compounds as a defence mechanism, called reflex bleeding (Al Abassi et al.…”
Section: Introductionmentioning
confidence: 99%